Noise environments in nursing homes: An overview of the literature and a case study in Flanders with quantitative and qualitative methods. (February 2020) - Thomas, Pieter; Aletta, Francesco; Filipan, Karlo; Mynsbrugge, Tara Vander; De Geetere, Lieven; Dijckmans, Arne; Botteldooren, Dick; Petrovic, Mirko; Van de Velde, Dominique; De Vriendt, Patricia; Devos, Paul
Abstract: As noise is a basic contributor to the evaluation of an environment, the indoor environment of a nursing home (where residents are provided with 24-hour functional support and care) is studied with this focus. General research results, as indicated from a literature review, are limited. Using quantitative and qualitative methods, five nursing homes in Flanders were studied before and after acoustic interventions. Sound levels were measured in individual bedrooms, living rooms and corridors to obtain the typical levels during a day. Acoustic intra-room performance parameters (reverberation time) and inter-room performance parameters (airborne noise insulation level and impact noise insulation level) were measured and compared with Belgian target values. The post operam measurements indicated the potential of the acoustic interventions (use of acoustic curtains, wall and ceiling panels, ventilation grills, floating floors) to improve the building performance and the acoustic climate. From a qualitative viewpoint, the thematic analysis of staff response to the acoustic interventions indicated direct positive outcomes (e.g., more pleasant, quieter indoor soundscapes) with both positive and negative outcomes from perceived indirect effects (i.e., non-acoustic factors).